CROSS-SECTIONAL STUDY ON THE ASSOCIATION BETWEEN INTERNET ADDICTION AND DEPRESSIVE SYMPTOMS IN ADOLESCENTS - Dr Rohan Gautam Shah, Dr Neil Gautam Shah, Dr Jagdish Nandkishore Gindodia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Internet addiction (IA) is an emerging public health concern amongadolescents, often associated with adverse mental health outcomes such as depression.Understanding this relationship is critical for early detection and intervention. Aim: To assessthe association between Internet addiction and depressive symptoms among adolescents.Methods: A cross-sectional study was conducted among 200 adolescents aged 13–18 years